Long-acting organic silicon water-based antirust agent and preparation method thereof

Through the polymerization and functional end capping reaction of organosilicon compounds, water-based anti-rust agents with high adhesion and density were prepared, which solved the problem of poor anti-rust effect of existing water-based anti-rust agents in high humidity and high heat environments, and achieved long-term efficient anti-rust and environmentally friendly use.

CN119553282APending Publication Date: 2025-03-04HUANGSHAN QIANGLI CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411739366.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing water-based anti-rust agents have poor anti-rust effect in high humidity and high heat environments, and most products require thick coating and high dosage, resulting in high cost and difficult sewage treatment.

Method used

The linear polymerization and chain extension reaction of organosilicon compounds such as dimethyldimethoxysilane, ethylene glycol, triethanolamine were used for linear polymerization and chain extension reaction, and functional capping reaction was carried out in combination with hydroxypropylprogyl ether and aminopropylmethyldiethoxysilane to prepare a high adhesion and density anti-rust film.

Benefits of technology

It realizes long-term rust prevention in a relatively harsh humid and hot environment, with an anti-rust time of up to 12 months, and is easy to use, low cost, and has a wide application market.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005162269420000021
    Figure BDA0005162269420000021
  • Figure BDA0005162269420000051
    Figure BDA0005162269420000051
  • Figure BDA0005162269420000061
    Figure BDA0005162269420000061
Patent Text Reader

Abstract

The invention relates to a long-acting organic silicon water-based antirust agent which is prepared by the following steps: polymerizing dimethyl dimethoxy silane, ethylene glycol, triethanolamine, trimethyl ethyoxyl silane, hydroxypropyl propargyl ether and aminopropyl methyl diethyoxyl silane to prepare an antirust functional component, and matching with a proper amount of emulsifier and water to prepare the water-based organic silicon antirust agent. The prepared antirust agent product is high in adhesive force after being attached to the metal surface, and due to the hydrophobic and anti-corrosion capacity of the organic silicon chain segment, a metal surface antirust film subjected to soaking treatment in a thin coating mode is high in density and long in antirust time, the antirust effect is good in a harsh damp and hot environment, and the antirust agent product can be applied to the metal surface. And the rust-proof film can be quickly removed by adopting hot water, the cost is low, the use is convenient, and the application market is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water-based rust prevention, and specifically relates to a long-acting organic silicon water-based rust inhibitor and a preparation method thereof. Background Art

[0002] Water-based rust prevention has been a major problem that has plagued the manufacturing industry at home and abroad for many years. The rust prevention period of most water-based rust preventives is generally 2-3 months, and the alkalinity is relatively strong. If the workpieces are placed in a high humidity, high heat, and stacked environment for a long time in the summer in the southern region, the phenomenon of stacked rust often occurs. In order to solve this problem, some products adopt the method of increasing the effective concentration and viscosity of the rust preventive liquid to achieve thick coating to prepare a thick film, in order to increase the thickness of the rust preventive film to improve the rust prevention effect. Generally, the film thickness of the rust preventive liquid reaches 20μm or even 25μm or more, resulting in a large amount of rust preventive liquid. On the one hand, the cost is high, and on the other hand, the amount of waste liquid after later cleaning is also large, which increases the difficulty of sewage treatment. Some products even add toxic nitrites, chromates, etc. to improve the performance of the rust preventive, which not only makes it difficult to treat sewage, but also the surface quality of the treated workpieces is poor. How to improve the rust prevention performance of water-based rust preventive liquid and achieve a lower film thickness such as less than 15μm, so as to achieve the rust prevention effect when the workpieces are stacked in a high humidity and high heat environment for a long time, has very important environmental and economic significance.

[0003] In view of the above-mentioned problems existing in the current water-based rust prevention industry, the present invention mainly utilizes the unique advantages of organosilicon compounds in rust prevention, and uses dimethyldimethoxysilane, ethylene glycol, triethanolamine, trimethylethoxysilane, hydroxypropyl propargyl ether, and aminopropylmethyldiethoxysilane to polymerize to prepare rust prevention functional components, and then mixes with an appropriate amount of emulsifier and water to prepare a water-based organosilicon rust inhibitor. The present invention first uses dimethyldimethoxysilane, ethylene glycol, etc. to carry out a linear polymerization reaction, and then carries out a chain extension reaction with triethanolamine to increase its branching degree, and then uses trimethylethoxysilane and hydroxypropyl propargyl ether to carry out a partial end-capping reaction, and finally adds aminopropylmethyldiethoxysilane for grafting and end-capping treatment to improve the adhesion to the metal substrate, and finally emulsifies with water and an emulsifier to obtain a water-based organosilicon rust inhibitor product. The rust inhibitor product prepared by the present invention has strong adhesion after being attached to the metal surface, and due to the hydrophobicity and anti-corrosion ability of the silicone chain segment, the rust-proof film on the metal surface treated by immersion is high in density and has a long anti-rust time. In a relatively harsh hot and humid environment, the anti-rust can be used for more than 12 months, the anti-rust effect is good, and the anti-rust film can be quickly removed by hot water. The cost is low and it is easy to use, and the application market is wide. Summary of the invention

[0004] The present invention relates to a long-acting organic silicon water-based rust inhibitor, which is prepared from raw materials comprising the following molar parts:

[0005]

[0006] It also includes appropriate amounts of emulsifier, deionized water and catalyst.

[0007] Furthermore, the emulsifier is a complex of sodium dodecylbenzene sulfonate and OP-10, and the mass ratio of the two is 0.3-0.5:1; deionized water is used to prepare a water-based rust inhibitor emulsion.

[0008] Furthermore, the amount of the emulsifier is 0.8-1.2% of the mass of dimethyldimethoxysilane; and the solid content of the water-based rust inhibitor prepared with deionized water is 10-15%.

[0009] Furthermore, the catalyst is potassium hydroxide, and the amount used is 0.2-0.3% of the mass of dimethyldimethoxysilane.

[0010] The method for preparing the long-lasting organic silicon water-based rust inhibitor as described above comprises the following steps:

[0011] A. Add the formulated amount of dimethyldimethoxysilane, ethylene glycol, xylene and catalyst into the reaction kettle, start stirring and heat to 100-105°C, then keep warm for polymerization reaction;

[0012] B. After removing the solvent from the sample, the viscosity of the polymer is tested. When the room temperature viscosity of the polymer reaches 150-180 mPa·s, a formulated amount of triethanolamine is added, and the temperature is raised to 120-125°C to carry out a chain extension polymerization reaction;

[0013] C. Take a sample and use gas chromatography to detect the content of triethanolamine. After the chain extension reaction is basically completed, add trimethylethoxysilane and continue to carry out hydrophobic end-capping reaction at 120-125°C;

[0014] D. Take a sample and use gas chromatography to detect the content of trimethylethoxysilane. When the conversion rate of trimethylethoxysilane reaches more than 95%, add the formulated amount of hydroxypropyl propargyl ether and aminopropyl methyl diethoxysilane, and continue to carry out functional end-capping reaction at 120-125° C.;

[0015] E. Sampling and detecting the content of hydroxypropyl propargyl ether by gas chromatography. When the conversion rate of hydroxypropyl propargyl ether reaches 98% or more, stopping the reaction, starting the vacuum system and removing the solvent and unreacted small molecule isosolvent under reduced pressure at 120-125° C.;

[0016] F. After no obvious substance is evaporated, release the vacuum, then cool down to 80-85°C, add the formulated amount of emulsifier and deionized water, stir at high speed to form an emulsion with a certain solid content, then cool down and discharge the material to obtain a milky white viscous liquid.

[0017] Furthermore, in step C, when the conversion rate of triethanolamine reaches more than 95%, the chain extension reaction is basically completed; in step E, the vacuum degree is controlled at -0.096 to -0.098Mpa; in step F, the solid content of the emulsion is 10-15wt%; and finally a milky white viscous liquid is obtained with a pH of 8-9.5.

[0018] For example, the preparation method of the long-lasting organic silicon water-based rust inhibitor comprises the following steps:

[0019] A. Add the formulated amount of dimethyldimethoxysilane, ethylene glycol, xylene and catalyst into the reaction kettle, start stirring and heat to 100-105°C, then keep warm for polymerization reaction;

[0020] B. After removing the solvent from the sample, the viscosity of the polymer is tested. When the room temperature viscosity of the polymer reaches 150-180 mPa·s, a formulated amount of triethanolamine is added, and the temperature is raised to 120-125°C to carry out a chain extension polymerization reaction;

[0021] C. Take a sample and use gas chromatography to detect the content of triethanolamine. When the conversion rate of triethanolamine reaches more than 95%, the chain extension reaction is basically completed, and then add trimethylethoxysilane to continue the hydrophobic end-capping reaction at 120-125°C;

[0022] D. Take samples and use gas chromatography to detect the content of trimethylethoxysilane. When the conversion rate of trimethylethoxysilane reaches more than 95%, add the formulated amount of hydroxypropyl propargyl ether and aminopropyl methyl diethoxysilane, and continue to carry out functional end-capping reaction for adhesion and anti-rust performance at 120-125°C;

[0023] E. Sampling and detecting the content of hydroxypropyl propargyl ether by gas chromatography. When the conversion rate of hydroxypropyl propargyl ether reaches more than 98%, the reaction is stopped, the vacuum system is started, and the solvent and unreacted small molecule isosolvent are removed under reduced pressure at 120-125° C., and the vacuum degree is controlled at -0.096 to -0.098 MPa;

[0024] F. After no obvious substance is evaporated, release the vacuum, then cool to 80-85°C, add the formulated amount of emulsifier and deionized water, stir at high speed to make an emulsion with a solid content of 10-15%, then cool and discharge the material, which is a milky white viscous liquid with a pH of 8.0-9.5.

[0025] The present invention also relates to the use of the long-lasting organic silicon water-based rust inhibitor as described above or the long-lasting organic silicon water-based rust inhibitor prepared by the preparation method as described above in an anti-rust film, especially as a long-lasting moisture and heat resistant water-based organic silicon rust inhibitor in an anti-rust film.

[0026] Beneficial Effects

[0027] The long-acting water-based silicone rust inhibitor of the present invention mainly uses dimethyldimethoxysilane, ethylene glycol, triethanolamine, trimethylethoxysilane, hydroxypropyl propargyl ether, and aminopropylmethyldiethoxysilane to polymerize to prepare anti-rust functional components, and then mixes with an appropriate amount of emulsifier and water to prepare a water-based silicone rust inhibitor. The present invention first uses dimethyldimethoxysilane and ethylene glycol to carry out a linear polymerization reaction, and then uses triethanolamine to carry out a chain extension reaction to increase its branching degree, and then uses trimethylethoxysilane and hydroxypropyl propargyl ether to carry out a partial end-capping reaction, and finally adds aminopropylmethyldiethoxysilane for grafting and end-capping treatment to improve the adhesion to the metal substrate, and finally emulsifies with water and an emulsifier to obtain a water-based silicone rust inhibitor product. The rust inhibitor product prepared by the present invention contains triethanolamine, hydroxypropyl propargyl ether and other groups with excellent rust prevention performance and adhesion in the molecular chain segment, and the aminopropylmethyldiethoxysilane introduced simultaneously introduces part of active amino groups into the molecular chain segment, thereby further enhancing the adhesion between the rust inhibitor molecules and the metal substrate and the compactness of the film-forming. Combined with the strong hydrophobicity and moisture and heat resistance of the organic silicon molecular chain segment, the final rust inhibitor product has not only strong adhesion after being attached to the metal surface, but also has high density and long rust prevention time of the rust prevention film on the metal surface treated by immersion only by thin coating due to the hydrophobicity and corrosion resistance of the organic silicon chain segment. In a relatively harsh humid and hot environment, the rust prevention can be used for more than 12 months, the rust prevention effect is good, and the rust prevention film can be quickly removed by hot water, the cost is low, the use is convenient, and the application market is wide.

[0028] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.

[0030] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.

[0031] Example 1

[0032] A long-lasting moisture and heat resistant water-based organosilicon rust inhibitor, comprising the following raw materials in molar parts:

[0033]

[0034] The emulsifier is a complex of sodium dodecylbenzene sulfonate and OP-10, and the mass ratio of the two is 0.5:1; deionized water is used to prepare the water-based rust inhibitor emulsion.

[0035] The amount of the emulsifier is 1.2% of the mass of dimethyldimethoxysilane; the solid content of the water-based rust inhibitor prepared with deionized water is 13.2wt%; the catalyst is potassium hydroxide, and the amount is 0.22% of the mass of dimethyldimethoxysilane.

[0036] The preparation method comprises the following steps:

[0037] A. Add the formulated amount of dimethyldimethoxysilane, ethylene glycol, xylene and catalyst into a reaction kettle, start stirring and heat to 105°C, then keep warm for polymerization reaction;

[0038] B. After removing the solvent from the sample, the viscosity of the polymer is tested. When the room temperature viscosity of the polymer reaches 150-180 mPa·s, a formulated amount of triethanolamine is added, and the temperature is raised to 125°C for chain extension polymerization reaction;

[0039] C. Take a sample and use gas chromatography to detect the content of triethanolamine. When the conversion rate of triethanolamine reaches more than 95%, the chain extension reaction is basically completed, and then add trimethylethoxysilane to continue the hydrophobic end-capping reaction at 125°C;

[0040] D. Take samples and use gas chromatography to detect the content of trimethylethoxysilane. When the conversion rate of trimethylethoxysilane reaches more than 95%, add the formulated amount of hydroxypropyl propargyl ether and aminopropyl methyl diethoxy silane, and continue to carry out functional end-capping reaction for adhesion and anti-rust performance at 125°C;

[0041] E. Sampling and detecting the content of hydroxypropyl propargyl ether by gas chromatography. When the conversion rate of hydroxypropyl propargyl ether reaches more than 98%, the reaction is stopped, the vacuum system is started, and the solvent and unreacted small molecule isosolvent are removed under reduced pressure at 125° C., and the vacuum degree is controlled at -0.096 to -0.098 MPa;

[0042] F. After no obvious substance is evaporated, release the vacuum, then cool down to 85°C, add the formulated amount of emulsifier and deionized water, stir at high speed to form an emulsion, then cool down and discharge the material.

[0043] The product is a milky white viscous liquid with a pH of 8.3.

[0044] Example 2

[0045] A long-lasting moisture and heat resistant water-based organosilicon rust inhibitor, comprising the following raw materials in molar parts:

[0046]

[0047] The emulsifier is a complex of sodium dodecylbenzene sulfonate and OP-10, and the mass ratio of the two is 0.5:1; deionized water is used to prepare the water-based rust inhibitor emulsion.

[0048] The amount of the emulsifier is 1.2% of the mass of dimethyldimethoxysilane; the solid content of the water-based rust inhibitor prepared with deionized water is 11.8wt%; the catalyst is potassium hydroxide, and the amount is 0.27% of the mass of dimethyldimethoxysilane.

[0049] The preparation method is the same as that of Example 1.

[0050] The obtained product is a milky white viscous liquid with a pH of 8.8.

[0051] Example 3

[0052] A long-lasting moisture and heat resistant water-based organosilicon rust inhibitor, comprising the following raw materials in molar parts:

[0053]

[0054]

[0055] The emulsifier is a complex of sodium dodecylbenzene sulfonate and OP-10, and the mass ratio of the two is 0.5:1; deionized water is used to prepare the water-based rust inhibitor emulsion.

[0056] The amount of the emulsifier is 0.8% of the mass of dimethyldimethoxysilane; the solid content of the water-based rust inhibitor prepared with deionized water is 14.6wt%; the catalyst is potassium hydroxide, and the amount is 0.26% of the mass of dimethyldimethoxysilane.

[0057] The preparation method is the same as that of Example 1.

[0058] The obtained product is a milky white viscous liquid with a pH of 9.4.

[0059] Example 4

[0060] A long-lasting moisture and heat resistant water-based organosilicon rust inhibitor, comprising the following raw materials in molar parts:

[0061]

[0062] The emulsifier is a complex of sodium dodecylbenzene sulfonate and OP-10, and the mass ratio of the two is 0.5:1; deionized water is used to prepare the water-based rust inhibitor emulsion.

[0063] The amount of the emulsifier is 1.2% of the mass of dimethyldimethoxysilane; the solid content of the water-based rust inhibitor prepared with deionized water is 12.9wt%; the catalyst is potassium hydroxide, and the amount is 0.24% of the mass of dimethyldimethoxysilane.

[0064] The preparation method is the same as that of Example 1.

[0065] The obtained product is a milky white viscous liquid with a pH of 9.1.

[0066] Comparative Example 1

[0067] b2 of Example 2 in ZL201510564084.6 is used as Comparative Example 1.

[0068] Comparative Example 2

[0069] Example 1 in ZL202210924103.1 is used as comparative example 2.

[0070] The anti-rust performance test is based on the single-piece and stacked anti-rust test in GB / T6144-2010 "Synthetic Cutting Fluid". The original solution of the product is used for anti-rust coating (dip coating method: the test piece is taken out directly after soaking for 5 minutes), and then the anti-rust film thickness and general anti-rust performance test are tested after sufficient drying at room temperature; while the wet heat anti-rust performance test is carried out in a constant temperature and humidity chamber, where the constant temperature is 30±2℃ and the relative humidity is 65±5℃. The demolding experiment is to soak the single-piece test piece in the anti-rust liquid and dry it, then place it at room temperature for 3 months, use 90-95℃ hot water, soak and stir for 20 minutes, then take out the workpiece to observe the residual anti-rust film. The results are shown in Table 1.

[0071] Table 1 Comparison of product performance between the embodiment and the comparative example

[0072]

[0073]

[0074] As can be seen from Table 1, the product of the present invention has good hydrophobic and anti-corrosion properties, and its use concentration is low. Its anti-rust film layer can achieve a better anti-rust effect when it is relatively thin at 10-15 microns. For example, the formed anti-rust film is relatively dense, and no rust spots are generated in 18 months for both single sheets and laminated sheets. In a special hot and humid environment, no rust spots are generated for single sheets after 6 months and laminated sheets after 4 months. It has excellent resistance to hot and humid rust and anti-rust properties, and can be smoothly removed in hot water, which is convenient to use. The product of comparative example 1 adopts a small molecule anti-rust component, which has strong hydrophilicity and insufficient water resistance, especially poor wet heat rust prevention performance, and both single sheets and stacked sheets are corroded; comparative example 2 adopts a thick film rust inhibitor product, which has a large molecular weight and high concentration, so the film thickness is basically about twice that of the product of the present invention. Its performance in conventional rust prevention is acceptable, but its water resistance is also insufficient in wet heat rust prevention, resulting in slight rust on the stacked sheets after 4 months. Compared with the product of the present invention, not only is the dosage large, but the subsequent environmental protection pressure is also greater, and the performance is also lower than the product of the present invention.

[0075] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.

Claims

1. A long-lasting organic silicon water-based rust inhibitor, characterized in that: The raw materials comprising the following molar compositions: It also includes appropriate amounts of emulsifier, deionized water and catalyst.

2. A long-lasting organic silicon water-based rust inhibitor as claimed in claim 1, further characterized in that the emulsifier is a complex of sodium dodecylbenzene sulfonate and OP-10 in a mass ratio of 0.3-0.5:1; and deionized water is used to prepare the water-based rust inhibitor emulsion.

3. A long-lasting organic silicon water-based rust inhibitor as claimed in claim 1 or 2, further characterized in that the amount of the emulsifier is 0.8-1.2% of the mass of dimethyldimethoxysilane; and the solid content of the water-based rust inhibitor prepared with deionized water is 10-15%.

4. A long-lasting organic silicon water-based rust inhibitor as claimed in claim 1 or 2, further characterized in that the catalyst is potassium hydroxide, and the amount used is 0.2-0.3% of the mass of dimethyldimethoxysilane.

5. The method for preparing a long-lasting organic silicon water-based rust inhibitor according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: A. Add the formulated amount of dimethyldimethoxysilane, ethylene glycol, xylene and catalyst into the reaction kettle, start stirring and heat to 100-105°C, then keep warm for polymerization reaction; B. After removing the solvent from the sample, the viscosity of the polymer is tested. When the room temperature viscosity of the polymer reaches 150-180 mPa·s, a formulated amount of triethanolamine is added, and the temperature is raised to 120-125°C to carry out a chain extension polymerization reaction; C. Take a sample and use gas chromatography to detect the content of triethanolamine. After the chain extension reaction is basically completed, add trimethylethoxysilane and continue to carry out hydrophobic end-capping reaction at 120-125°C; D. Take a sample and use gas chromatography to detect the content of trimethylethoxysilane. When the conversion rate of trimethylethoxysilane reaches more than 95%, add the formulated amount of hydroxypropyl propargyl ether and aminopropyl methyl diethoxysilane, and continue to carry out functional end-capping reaction at 120-125° C.; E. Sampling and detecting the content of hydroxypropyl propargyl ether by gas chromatography. When the conversion rate of hydroxypropyl propargyl ether reaches 98% or more, stopping the reaction, starting the vacuum system and removing the solvent and unreacted small molecule solvent under reduced pressure at 120-125° C.; F. After no obvious substance is evaporated, release the vacuum, then cool down to 80-85°C, add the formulated amount of emulsifier and deionized water, stir at high speed to form an emulsion with a certain solid content, then cool down and discharge the material to obtain a milky white viscous liquid.

6. The method for preparing a long-lasting organic silicon water-based rust inhibitor as claimed in claim 5, further characterized in that in step C, when the conversion rate of triethanolamine reaches more than 95%, the chain extension reaction is basically completed.

7. The method for preparing a long-lasting organic silicon water-based rust inhibitor according to claim 5, further characterized in that in step E, the vacuum degree is controlled at -0.096 to -0.098 MPa.

8. The method for preparing a long-lasting organic silicon water-based rust inhibitor as claimed in claim 5, further characterized in that in step F, the solid content of the emulsion is 10-15wt%; and finally a milky white viscous liquid is obtained with a pH of 8-9.

5.

9. Use of the long-acting organic silicon water-based rust inhibitor according to any one of claims 1 to 4 or the long-acting organic silicon water-based rust inhibitor prepared by the preparation method according to any one of claims 5 to 8 in an anti-rust film.

Citation Information

Patent Citations

  • A kind of citric acid polyol ester for ferrous metal antirust, water-based antirust agent and preparation method thereof

    CN105198749B

  • Long-acting thick-film water-based antirust agent and preparation method thereof

    CN115261866A